Respuesta :

Answer:

Step-by-step explanation:

5

+

1

=

3

+

7

5x+1=3x+7

Solve

1

Subtract  

1

1

from both sides of the equation

5

+

1

=

3

+

7

5x+1=3x+7

5

+

1

1

=

3

+

7

1

5x+1{\color{#c92786}{-1}}=3x+7{\color{#c92786}{-1}}

2

Simplify

Subtract the numbers

Subtract the numbers

5

=

3

+

6

5x=3x+6

3

Subtract  

3

3x

from both sides of the equation

5

=

3

+

6

5x=3x+6

5

3

=

3

+

6

3

5x{\color{#c92786}{-3x}}=3x+6{\color{#c92786}{-3x}}

4

Simplify

Combine like terms

Combine like terms

2

=

6

2x=6

5

Divide both sides of the equation by the same term

2

=

6

2x=6

2

2

=

6

2

\frac{2x}{{\color{#c92786}{2}}}=\frac{6}{{\color{#c92786}{2}}}

6

Simplify

Cancel terms that are in both the numerator and denominator

 

Solution

=

3

the answer is x = 3
Ver imagen urlocalgenius